2006
DOI: 10.1136/ip.2006.012617
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from violence in North Carolina, 2004: how deaths differ in females and males

Abstract: Objective: To identify gender differences in violent deaths in terms of incidence, circumstances, and methods of death. Design: Analysis of surveillance data. Setting: North Carolina, a state of 8.6 million residents on the eastern seaboard of the US. Subjects: 1674 North Carolina residents who died from violence in the state during 2004. Methods: Information on violent deaths was collected by the North Carolina Violent Death Reporting System using data from death certificates, medical examiner reports, and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 13 publications
(7 reference statements)
2
26
2
4
Order By: Relevance
“…The extent of non-firearm-related homicides that involve intimate partner violence should be clarified, where homicide may possibly happen after fights between partners. A study of deaths from violence in North Carolina and other reports showed that intimate partner violence played a key role in the majority of female homicides 19 20 21. Sex-specific homicide-prevention strategies should take into account these findings when women are more likely than men to be the victims of non-firearm-related rather than firearm-related homicide.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of non-firearm-related homicides that involve intimate partner violence should be clarified, where homicide may possibly happen after fights between partners. A study of deaths from violence in North Carolina and other reports showed that intimate partner violence played a key role in the majority of female homicides 19 20 21. Sex-specific homicide-prevention strategies should take into account these findings when women are more likely than men to be the victims of non-firearm-related rather than firearm-related homicide.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on deaths from violence in North Carolina and the different epidemiologic patterns of death for males and females revealed that approximated 13% of all male homicides involved IPV in some way and that 4% of men killed were directly killed by an intimate partner. 63,64 Men also sustain injuries inflicted by their intimate partners, but these injury patterns have not been well studied. 65 Coker et al re-examined the NVAWS data to determine the physical and mental health effects of both physical and psychological IPV victimization on men and women.…”
Section: Health Effects Associated With Ipv Victimization Of Menmentioning
confidence: 99%
“…The NVDRS is the first data system to link multiple sources to provide a comprehensive assessment of factors that are associated with violent death 16. Remarkably, few studies have used the NVDRS to address the circumstances surrounding suicide mortality 17 18 19 20. Equally important, none of the studies has examined the factors associated with suicides involving firearms.…”
mentioning
confidence: 99%